The rights and responsibilities of spouses in Islam - Karim, Fatimah (Mission Soft Foundation, 2024)
Marriage in Islam is a sacred institution that forms the cornerstone of a stable and harmonious society. It signifies mutual rights and responsibilities, creating a reciprocal relationship designed to foster mutual respect, love, and understanding. The guidelines provided by the Quran, Hadith, and Islamic jurisprudence ensure that both spouses fulfill their roles in a manner pleasing to Allah. This article explores these rights and responsibilities, drawing upon primary Islamic sources and scholarly works to provide a comprehensive understanding.